PENDIDIKAN KESEHATAN SEBUAH PENDEKATAN/NILAI UNTUK MENINGKATKAN PENGETAHUAN PENCEGAHAN PENULARAN TB PARU PADA ANGGOTA KELUARGA KONTAK SERUMAH - Nur Fadhilah; Abdul Razak Muttalif; Faridah Hashim (Universitas Muhammadiyah Pringsewu, 2023)
Background: TB cases in Indonesia reached 845,000 people, of which only 69% were identified, meaning cases that have not been found have the potential for transmission. The main source of transmission is positive smear TB patients; Family members are the group most susceptible to infection. Low knowledge about TB has various impacts, namely: the belief that pulmonary TB is a hereditary disease, not an infectious disease. As a result, sufferers and their families live with risky habits (sleeping with sufferers, coughing without covering their mouths, not wearing masks, throwing phlegm anywhere). Poor knowledge results in delays in patient treatment thereby increasing the risk of transmission. Purpose: The aim of this study was to evaluate the effect of pulmonary TB health education on knowledge of prevention of pulmonary TB transmission. Methodology: The research design used a sequential explanatory mixed method. A total of 260 respondents were involved in this study, divided into two experimental and control groups. Health education interventions were given to the experimental group, while the control group was only given leaflets containing information about TB. Results: The average knowledge after the intervention showed that the experimental group had a higher level of knowledge than the control group. The statistical test results showed that there was a significant difference in knowledge after the study was conducted on the control group and the experimental group (p = 0.000). The increase in knowledge of the experimental group was higher than the control group, this indicates that health education is effective in increasing knowledge about pulmonary TB in families. Conclusion: Health education that is carried out in a structured manner involving the active role of the family is effective in increasing knowledge about prevention of pulmonary TB transmission.